(untitled) (Journal of the College of Basic Education, 2023)
By Using CORSIKA Program, the simulation of Cherenkov light Lateral distribution Function (LDF) of Cherenkov Light in Extensive Air Showers (EAS) of primary protons is performed at the very high energy range (). The approximation that constructed on the basis of this simulation have allowed us to reconstruct the events, that is, to reconstruct the type and energy of the particle that generated EAS from signal amplitudes of Cherenkov light registered with the Tunka-25 facility. The extrapolation of the Cherenkov light LDF approximation at the energy range () was taken into account.